Financial services: Global perspectives - Moshirian, Fariborz (Journal of Banking & Finance, 2004)
The purpose of this paper is to discuss the issues related to the deregulation of the financial services sector and the role of multilateral negotiations which has opened up opportunities for the expansion of international financial services. The paper analyses various categories of international financial services and highlights those factors that contribute to an increase in the competitiveness of financial institutions in their attempt to increase the supply of international financial services. The paper also analyses the complementary role of FDI and trade in international financial services and discusses some of the benefits of FDI in financial services that have led to a more efficient and more competitive financial services industry in the host countries.